THE 1.5 GENERATION'S MEMORY OF THE GDR: CHILD VICTIMS TESTIFY TO THE EXPERIENCE OF FORCED EXILE. (January 2015) - Jilovsky, Esther; Lewis, Alison
ABSTRACT This article investigates the legacy of violence in the children of East German refugees, émigrés and victims of persecution exiled from the German Democratic Republic in the 1970s and 1980s. Through the analysis of Susanne Schädlich's memoir Immer wieder Dezember: der Westen, die Stasi, der Onkel und ich (2009) and the essay collection Ein Spaziergang war es nicht: Kindheiten zwischen Ost und West (2012) edited by Schädlich and her sister Anna Schädlich, we argue that this testimony reveals a distinct generational cohort. This age group (born between the mid‐1960s and early 1980s) is shaped by their parents' experience of persecution, but also by the loss of the country of their childhood. Rather than a second generation memory this generation constitutes a 1.5 generation memory of the GDR. This can be characterised on the one hand as a type of traumatic memory stemming from the exile experience shared by both parents and children. On the other hand these memories constitute a counter‐narrative to 'Ostalgie', forming a bridging link between the dominant 'Diktaturgedächtnis' and what Martin Sabrow has called the 'Arrangementgedächtnis'. In contrast to the 'Wendekinder' and 'Dritte Generation Ost', the 1.5 victim generation of the GDR bears a double burden: the effects of the hardship of exile are compounded by, rather than alleviated by, the fall of the Wall.